Mauritania Transport Policy Note - World Bank (World Bank, Washington, DC, 2021)
Mauritania, a country sparsely populated of 4.5 million people and a sustained growth of 60.4 percent in its urbanization rate, increasingly relies on enhancements in its transport connectivity among and within its urban areas to realize its economic potential and the improvement of its human capital indicators. Indeed, 90 percent of goods are transported by road, as so do 80 percent of passengers. Thirty five percent of Mauritania’s population lives in Nouakchott. Connectivity within the city is challenging leaving many away from economic opportunities. In this context, the Government of Mauritania and the World Bank held exchanges and discussions over the last ten months towards the identification and analysis of challenges and opportunities in transport connectivity focusing largely on road maintenance and urban mobility in Nouakchott. This note summarizes the results of those exchanges and discussions.